Networks, Firms, and Trade - Bastos, Paulo; Silva, Joana (World Bank, Washington, D.C., 2013)
Fixed costs associated with learning about demand and setting up distribution networks are expected to be lower when there are more potential contacts in the destination market, suggesting a greater probability of market entry and larger export revenues. The authors match historically-determined emigration stocks with detailed firm-level data from Portugal to examine the effect of migrant networks on these export outcomes. They find that larger stocks of emigrants in a given destination increase export participation and intensity. In addition, they show that the former of these effects tends to be more pronounced among firms that are more likely to have close ties with the emigrants. These results are consistent with a multiple-destination version of the Melitz (2003) model featuring market-specific entry costs and idiosyncratic firm-destination demand shocks.